Handwritten characters extraction from form based on line shape characteristics - Al-Faris, Ali Qusay (Science Publications, 2011)
Data entry form is a convenient and successful too l for information collection by filling in the sheets using pen and h andwriting. One of the most important fields in the se forms is the data filled boxes. Extracting the hand writing from the data entry forms is important for many purposes such as in documenting and archiving. The extraction process is also important in situations such as when it is necessary to the hand written recognition process. Approach: A simple and effective approach is presented to extract hand written characters, including digits and letters of any language from data filled boxes of data entry f orm and to deal with cases of overlaps between the handwritten characters and boxes’ lines. The propos ed approach is based on line shape characteristic by detecting and removing the vertical and horizont al straight boxes’ lines, while preserving the curved lines which represent the handwritten charac ters. The problem of the handwritten characters overlapping with the data filled boxes’ line is sol ved using morphology dilation to reconstruct the broken characters after the removal of the boxes’ l ines. Results: Experimental results have demonstrated that the proposed approach can extract handwriting from data filled boxes with overall 94.052% for data collection of 150 forms. Conclusion: The proposed algorithm has been successfully implemented and tested to achieve the objectives of handwritten extraction of any language from data filled boxes. However, this work could not deal wit h situations whereby the characters touch other immediate characters.